Comparison of clarithromycin triple therapy and levofloxacin triple therapy in H. pylori eradication. - عثمان, سيف; حماد , اسماعيل; عيسى , رنا (Latakia University Journal -Medical Sciences Series, 2022)
Background: Helicobacter pylori is one of the bacteria widely spread around the world, and it plays an important role in several pathological conditions such as peptic ulcer disease, dyspepsia and neoplastic metaplasia in the stomach.Different treatment regimens are used to eradicate H. pylori all over the world, and the first line of treatment varies according to the region and the country due to the difference in the availability of medicines and the resistance of H. pylori to antibiotics.The most common treatment regimens used in Syria are the standard triple therapy with clarithromycin and the triple therapy based on levofloxacin The Goal Of The Study: Comparison of the effectiveness of standard triple therapy with clarithromycin and levofloxacin based triple therapy in eradication of H. pylori Methods: The study included 117 patients from the Digestive Diseases Division at Tishreen University Hospital for the year 2020 who were given an upper gastrointestinal endoscopy with biopsies taken to investigate Helicobacter pylori infection The sample of H. pylori positive patients was divided into two groups: Group A was put on the standard triple therapy of clarithromycin (Cla500mg *2, Amo 1000mg *2and esostome40 mg *1) for 14 days, and group B was put on the triple therapy based on levofloxacin (Levo500mg *1, Amo1000mg *2 and esostome 40mg *1) for 14 days. All patients had upper GI endoscopy repeated 4-6 weeks after the end of treatment, with 5 tissue biopsies taken to investigate Helicobacter pylori Results and discussion: The study included 117 patients who fulfilled the inclusion criteria. Among these patients, H. pylori infection was positive in 86 patients, with a percentage of 73.5%. Pylori-negative patients were excluded, and the sample of H. pylori-positive patients was divided into two groups: Group A was placed on the standard triple therapy with clarithromycin for 14 days, and group B was placed on the triple therapy based on levofloxacin for 14 days. 17 patients out of 46 patients from group A were cured, with an eradication rate of H. pylori that reached 37%, and 18 patients out of 40 patients in group B were cured with an eradication rate of H. pylori that reached 45%. The study did not show statistically significant differences between the incidence of recovery and sex (P = 0,7), as well as between the incidence of recovery and age (P = 0,1) Conclusion:The triple therapy based on levofloxacin showed superiority to the standard triple therapy with clarithromycin in eradicating H. pylori (45% versus 37% eradication rate, respectively).